IbM KELOMPOK PETANI TAMBAK dan NELAYAN DESA KALANGANYAR KECAMATAN SEDATI KABUPATEN SIDOARJO JAWA TIMUR - Karyanto, Yunus; Widyastuti, Sri (LPPM Universitas PGRI Adi Buana Surabaya, 2014)
Location IbM activities in the Village District of Sedati Kalanganyar Sidoarjo in East Java. Specific targets and outcomes that would result from the application of this IbM is (1) liquid smoke as a natural preservative of food and other uses, (2) charcoal briquettes as an alternative fuel, (3) sales strategy and simple bookkeeping The method primarily used to achieve the objectives of this IbM activities are as follows: to achieve the first goal, the method used is to conduct awareness about environmental hygiene, especially not throw garbage / waste indiscriminately. To achieve the second goal, this method is the explanation equipment manufacture liquid smoke, how to make liquid smoke, liquid smoke making training, training preserving fish with liquid smoke. To achieve the third goal, this method is the training procedures for packaging into briquette charcoal, charcoal briquettes use of training materials and the provision of sales strategy and simple bookkeeping. Implementation of training activities have managed to make liquid smoke and charcoal briquettes from agricultural-waste and this activities increase the income of fishermen and fish farmers and environmental conditions to be cleaner